Thermal behavior of phase change material in open cavities: Effects of opening position and occupancy level - Kiyak, Burak; Öztop, Hakan Fehmi; Biswas, Nirmalendu; Selimefendigil, Fatih (Elsevier, 2025)
Understanding the thermal behavior of Phase Change Materials (PCMs) within open cavities is critical for optimizing energy storage systems. This research examines the effects of different cavity opening positions (side, corner and top) and varying levels of PCM occupancy (fully filled, 75 %, and 50 % filled) on the melting and heat transfer performance. A numerical model, based on a finite volume approach, is developed using a melting framework to simulate the phase change process of PCM in a stagnant air environment. The air temperature was kept constant at 5 degrees C, while the initial PCM temperatures were adjusted to 5 degrees C, 10 degrees C, and 15 degrees C. The analysis primarily focuses on how these variables influence the melting rate, energy storage efficiency, and heat transfer characteristics. The findings reveal that the position of the cavity opening significantly impacts thermal behavior, with the corner opening offering faster melting and more efficient heat transfer compared to the side and top configurations. Additionally, the initial temperature of the PCM strongly influences the melting process, with higher starting temperatures leading to quicker phase transitions and increased energy storage capacity. It is also observed that fully filled cavities enhance energy storage but slow down the melting process. The case with 50 occupancy reduces the melting time upto 75 % to store 240 kJ/kg stored energy compared to full occupancy. This study provides practical insights for improving the design of PCM-based energy storage systems by optimizing cavity positioning and occupancy levels. Future research may explore alternative geometries, materials, and environmental conditions to further enhance PCM applications in energy efficiency and thermal management.
Keywords: Open cavity; Phase Change Material (PCM); Thermal behavior; Heat transfer; Melting process